2021
DOI: 10.46328/ijres.2287
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Innovative Learning on Mathematical Problem-Solving Ability: A Meta-Analysis

Abstract: Learning problem-solving skills emphasizes reasoning abilities to determine conclusions based on-premises, determining alternative solutions in decision making, thinking creatively in building alternatives to get keys, and critical thinking to evaluate the best solutions in answering problems. This study aims to identify biased publications using the trim and fill method in determining the effectiveness of learning on the problem-solving abilities of junior high school students. This research is a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…The students learn how to work as teams to achieve a single goal. These results support the concept of cooperative learning usage within classrooms (Ridwan, et al, 2021). It is seen that cooperative learning impacts positively on the academic performance of mathematics students (Zhu & Kaiser, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…The students learn how to work as teams to achieve a single goal. These results support the concept of cooperative learning usage within classrooms (Ridwan, et al, 2021). It is seen that cooperative learning impacts positively on the academic performance of mathematics students (Zhu & Kaiser, 2022).…”
Section: Discussionsupporting
confidence: 80%
“…From the results of the picture above that there is an increase in each indicator of the ability to think creatively both from thinking fluently, thinking flexibly, thinking original, and thinking in detail after getting treated with the case method in learning mathematics. Critical thinking is a constructive way to find the right solution, by evaluate all criteria to answer the problem (Ridwan et al, 2021).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%
“…The measurable variables in the study consisted of learning outcomes and social and emotional skills. Several researchers have conducted a meta-analysis evaluation of cooperative learning utilising moderator factors at all levels of education so far (Capar and Tarim, 2015;Hattie, 2009;Mansurah et al, 2021;Setiana et al, 2020;Sharan, 2010;Turgut and Turgut, 2018) as well as on student learning outcomes, with a focus on cognitive and emotional development (Parveen, Yousuf and Mustafa, 2017;Ridwan et al, 2021;Vega and Hederich, 2015). In comparison to the tertiary level, Hattie (2009) found that the cooperative learning approach for elementary and high school students was appropriate.…”
Section: Review Studymentioning
confidence: 99%